IDENTIFIKASI DRUG RELATED PROBLEMS (DRPs) PADA PASIEN ANAK GASTROENTERITIS AKUT DI INSTALASI RAWAT INAP RSU ANUTAPURA PALU - Arlinda Arlinda; Alwiyah Mukaddas; Ingrid Faustine (Universitas Tadulako, 2016)
Acute gastroenteritis, one of the most common disease in children and one of the causes of children’s death in the world, has a great chance of the occurrence of Drug Related Problems (DRPs). This study aimed to determine the incidence of potential DRPs occurred in pediatric inpatients of acute gastroenteritis in Anutapura General Hospital, Palu, Central Sulawesi. This was a prospective observational study done by collecting primary data from the observation and secondary data from medical records of pediatric inpatients aged from 1 month to 14 years and diagnosed with acute gastroenteritis with or without dehydration. Data were then analyzed and descriptively presented including drug use without indication, wrong drug, drug dose too low, drug dose loo high, and untreated indication. The results showed that there were 115 cases of DRPs. The most DRPs found was drug use without indication as many as 56 cases (48.7%), while the others successively were drug dose too low 26 cases (22.6%), untreated indication 16 cases (14%), drug dose too high 15 cases (13%), and wrong drug 2 cases (1.7%)